Analysis Of The Effect Of Assets Structure, Capital Structure, And Liquidity On Company Value With Profitability As Intervening VariablesOn F&B Companies Listed On Idx For The 2017-2021 Period - Isieny Wendy; Nagian Toni; Enda Noviyanti Simorangkir (TRIGIN PUBLISHER, 2022)
This study aims to analyze the Analysis of the Effect of Asset Structure, Capital Structure, and Liquidity on Firm Value with Profitability as an Intervening Variable in F&B Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period. The population in the research conducted are 26 Food & Beverage companies listed on the IDX for the 2017-2021 period. The technique used in sampling is purposive sampling. The number of samples in this study were 10 F&B companies so that the number of observations made was 10 x 5 = 50 observations of F&B companies listed on the IDX for the 2017-2021 period. The data analysis tool uses Partial Least Square (PLS). The results of the analysis show that the asset structure does not affect the profitability of F&B companies listed on the IDX for the 2017-2021 period. The capital structure affects the profitability of F&B companies listed on the IDX for the 2017-2021 period. Liquidity affects the profitability of F&B companies listed on the IDX for the 2017-2021 period. Profitability has an effect on firm value in F&B companies listed on the IDX for the 2017-2021 period. Asset structure affects the firm value of F&B companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Capital structure affects the firm value of F&B companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Liquidity has no effect on firm value in F&B companies listed on the IDX for the 2017-2021 period. The asset structure has no effect on the value of the company which is intervened by the profitability of the F&B companies listed on the IDX for the 2017-2021 period. The capital structure affects the value of the company which is intervened by the profitability of F&B companies listed on the IDX for the period 2017-2021. Liquidity affects the value of the company which is intervened by the profitability of F&B companies listed on the IDX for the 2017-2021 period.